The transformation of LGBTQ+ relationships in Turkey from digital dating to digital violence - Gümüş, Burcu (Journal of family violence, 2024)
Purpose: This study aims at ascertaining the kinds of violence LGBTQ + individuals suffer in relationships formed via dating apps and how this violence arises, as well as the differences in coping based on age, ethnicity, and gender identity. Methods: The data for this qualitative study were collected using 50 face-to-face in-depth interviews with LGBTQ + persons between the ages of 18-55 living in Istanbul. Results: Violence includes physical and sexual assault, hate speech, hate crime and romance fraud. Young people ages 18 to 24, trans women and of different ethnicities encountered more than one type of violence concurrently. Older people ages 42 to 55 more often experienced romance fraud, whereby they had to provide financial support to their partners despite not wanting to stay in the relationship. While coping strategies varied, trans women and LGBTQ + persons having different ethnic origins tended to accept and internalize their situations, primarily due to being marginalized by the healthcare services and law enforcement. Subjects ages 42 to 55 accepted the economic consequences of romance fraud since they felt there was no other way to have the relationship they desired. Conclusions: Age, ethnicity and gender identity were the major factors in the type and severity of violence arising in relationships formed via dating apps. Research shows that dating apps intrinsically do not spawn the violence directed at LGBTQ + people. Rather it is homophobic, transphobic or xenophobic state practices that lead to violence against the LGBTQ + community.